Numerical Analysis of Time-Fractional Diffusion Equations via a Novel Approach. (27th May 2021) - Shah, Nehad Ali; Saleem, S.; Akgül, Ali; Nonlaopon, Kamsing; Chung, Jae Dong
Abstract : The aim of this paper is a new semianalytical technique called the variational iteration transform method for solving fractional-order diffusion equations. In the variational iteration technique, identifying of the Lagrange multiplier is an essential rule, and variational theory is commonly used for this purpose. The current technique has the edge over other methods as it does not need extra parameters and polynomials. The validity of the proposed method is verified by considering some numerical problems. The solution achieved has shown that the better accuracy of the proposed technique. This paper proposes a simpler method to calculate the multiplier using the Shehu transformation, making a valuable technique to researchers dealing with various linear and nonlinear problems.